Protein Content of Cervicovaginal Fluid Is Altered During Bacterial Vaginosis - Tafner Ferreira, Carolina Sanita [UNESP]; Silva, Marcia Guimaraes da [UNESP]; Pontes, Leticia Gomes de [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Marconi, Camila [UNESP] (Lippincott Williams & Wilkins, 2018)
Objectives The aim of the study was to compare, using a proteomic approach, cervicovaginal fluid (CVF) proteins of women with bacterial vaginosis (BV) with those presenting normal microbiota. Materials and Methods A total of 309 reproductive-aged women were cross-sectionally enrolled. Participants were tested for vaginal candidosis, Trichomonas vaginalis, Chlamydia trachomatis, and Neisseria gonorrhoeae and excluded if positive. Vaginal microbiota was classified microscopically according to Nugent criteria in normal, intermediate, and BV. Randomly selected CVF samples of 29 women with BV and an equal number with normal microbiota were subjected to proteomic analysis. Thus, a total of 58 CVF samples were evaluated using shotgun liquid chromatography-tandem mass spectrometry in a Q-Tof PREMIER API mass spectrometer (MicroMass/Waters) for peptide detection and relative quantification. Results Of the 309 women enrolled, 63 (20.4%) were excluded after testing positive for at least one of the tested co-infections or because of low-quality samples. Microscopic classification of vaginal microbiota on the remaining 246 samples revealed that 132 women (53.6%) had normal microbiota, 33 (13.4%) had intermediate microbiota, and 81 (33.0%) had BV. Proteomic analysis of CVF of 58 randomly selected women with normal microbiota (n = 29) or BV (n = 29) successfully identified 74 proteins. In addition, the comparison of abundance of those proteins between the groups showed that the following five (6.7%) were enriched in BV: neutrophil elastase, kaliocin-1, neutrophil defensin-1, Ig lambda-2 chain C regions, and protein S100-A7. All of which have a recognized role in host's immunity. Conclusions Exclusive finding of BV affects immunity-related CVF components of reproductive-aged women.
Keywords: vaginal microbiota; bacterial vaginosis; proteomics; shotgun mass spectrometry